Metaphors that prospective primary school teachers possess on the concept of 'mathematics' - ŞENGÜL, SARE (ELSEVIER SCIENCE BV, 2012)
The main purpose of this study is to reveal the thoughts that prospective teachers studying at the department of teaching mathematics at primary schools possess with respect to the concept of 'Mathematics' through metaphors. The study was carried out with 106 female and 44 male students, total of 150 prospective teachers, who study at Kocaeli University Educational Faculty, Department of Teaching Mathematics at Primary Schools, during the fall semester in the 2011-2012 academic year. The data for the study was obtained by having students complete the blanks in the sentence 'Mathematics is like .......; Because .......'. The study had a descriptive nature, since it is an attempt to reveal an existing situation as it is. The metaphors developed by the participant prospective teachers on the concept of 'mathematics' were analyzed and interpreted by using qualitative research methods under the positive, negative and conceptual categories. In this context, the perceptions of prospective teachers studying at the department of teaching mathematics at primary schools regarding the concept of mathematics provide different perspectives. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Metaphor; mathematics; prospective mathematics teachers